Crazing level after pin insertion in anterior primary teeth: a preliminary in vitro study - Ansari, Ghassem; Mashhadi Abbas, Fatemeh; Malekafzali, Beheshteh; Yarmohammadi, Reza (Journal of Dental School, 2019)
Objectives This study aimed to investigate dentinal crack rate following parapulpal pin insertion in anterior primary teeth. Methods Thirteen sound freshly extracted primary canine teeth were horizontally sectioned 1 mm above the cementoenamel junction (CEJ). All samples were thoroughly inspected to ensure that the teeth had no cracks. The teeth were then mounted in acrylic blocks, and subjected to drilling and insertion of a single parapulpal pin in the prepared hole. The teeth were then sectioned perpendicular to the already prepared surface at 1, 2 and 3 mm depths for further evaluation under a stereomicroscope (x12 and x25 magnifications). Results No crack or crazing was observed in teeth in the control group while one out of 11 teeth in the case group had a crack. Conclusion The use of 0.53 mm diameter self-threading pin did not increase the risk of crack formation in dentin of anterior primary teeth prior to composite restoration.